MODIFIED SORBENTS AND THEIR APPLICATION FOR EXTRACTION OF METAL IONS - N. C. Murzakassymova; N. A. Bektenov; M. A. Gavrilenko (Academic Scientific Journal of Chemistry, 2021)
. The data on accumulated mining waste in the territory of Kazakhstan are presented. Their processing has become very important in our time. The structure of surface-modified carbon materials with a grafted layer is given. New modified carbon sorbents were obtained, oleum was used as a modifying agent. It was revealed that the capacitive characteristics of the modified sorbent are significantly higher than that of the original one, which will make it possible to more efficiently extract the metal ion from wastewater and technogenic formations. Sorption is an effective method of extracting valuable components from wastewater and man-made formations. This method allows you to recover valuable substances with a high degree of wastewater treatment, which can be purified to the maximum permissible concentration of pollutants and then used in technological processes or in recycling water supply systems. Processing involves ores characterized by a low content of valuable components, fine dissemination and similar technological properties of minerals. The existing technologies for the development of minerals make it possible to use only a small part of the valuable mineral mass extracted from the subsoil, and the rest forms waste, which, as it accumulates and is stored, becomes one of the most significant factors of anthropogenic changes in the environmen